Analiza plavanja na 400 m prosto pri predmetu Plavanje 1 z osnovami reševanja iz vode - Foški, Tajda (Šport (Ljubljana), 2018)
The aim of the study was to analyse swimming technique and obtained times of students of Faculty of sport at the practical exam where they have to swim 400 m freestyle. Only the students who successfully finished the exam in the year 2016/2017 were included in the study. Students measured each other and collected all data on a sheet. They had to note swimming technique (breaststroke, backstroke, freestyle) and time for each distance. The main idea was to obtain which techniques students choose for their exam. Moreover, if the final time is affected by swimming techniques and if there are any differences regarding the gender. We obtained that students choose all three techniques, some swam in just one technique and the others combined two or three techniques. Most students (56%) chose to combine strategies and the most popular was the combination of breaststroke and front crawl (75%). Analysis showed that the average final time of front crawl was more than a minute shorter than the times of breaststroke and combined strategies. Regarding the gender, more males chose front crawl than females and vice versa. There was no difference for the combining strategies.
Keywords: 400 m prosto; izpit; metabolični procesi; plavalne tehnike; plavanje; šport; študentje